EVALUASI PENGGUNAAN OBAT ANTI HIPERTENSI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Supadmi, Woro (Universitas Ahmad Dahlan, 2011)
The intervention led to various complications in dialysis patients includehypertension intradialitik as a result of hemodynamic changes.The phenomenon of theparadox of which caused activation of endogenous vasopresor due to changes involume status and antihypertensive medication terdialisisnya factor. This study aims todetermine patterns of use of antihypertensive drugs, evaluating the rationality and sideeffects of antihypertensive drugs based on literarur. This study was performed with thepatientâs condition based on the observation of patients to see medical records drugdata, laboratory data of patients and patientâs condition.Retrospective study ofhemodialysis patients in the hospital PKU Muhammadiyah Yogyakarta year periodfrom 2009 to 2010. Patients according to inclusion criteria, anti-hypertensive drugreceipts and complete medical record data. Evaluation of rationality involves the use ofantihypertensive drugs right dose, right patient and side effects based on the DrugInformation Hand Book 2005, Handbook of Clinical Drug Data, 2002. The study found60 patients who fit the inclusion criteria. Based on the research patterns of use ofantihypertensive drugs in patients with hemodialysis is captoril, furosemide, nifedipine,lisinopril, amlodipine, valsatran and clonidin. Evaluation rationality inappropriate useof drugs dose use of captopril 11 patients of 34 patients and furosemide 18 patients from52 patients, inappropriate use of captopril patients was 9 patients of 34 patients.Sideeffects that occur in patients with hypokalemia due to the use of furosemide is 40patients, cough due to captopril was 13 patients, side effects of nifedipinegastrointestinal disorders cough and 11 patients, 5 patients coughlisinopril. Conclusion:he use of antihypertensive medications in hemodialysispatientsat RSU PKU Muhammadiyah Yogyakarta is rational.